6.1: Invited Paper: Dynamic Optical Devices for AR/VR Applications. (28th November 2018) - Huang, Yi-Pai; Wu, Jui-Yi; Chou, Ping-Yen; Peng, Kuei-En
Abstract : Light field near eye displays (LFNED) can produce lightweight devices and address the accommodation‐convergence conflict. However, low spatial resolution and narrow FoV creates a poor immersive experience in LFNED. In this paper, the dynamic optical components are proposed to enhance image resolution and widen the FoV of LFNED. The proposed devices are the flat and thin component with only few mm of thickness, which could be placed in the gap of LFNED without increasing the thickness. The results show that the proposed components could be easily integrated in LFNED with the effect of resolution and FoV enhancement..